Boosting BCG with recombinant modified vaccinia ankara expressing antigen 85A: different boosting intervals and implications for efficacy trials. - Ansar A Pathan; Clare R Sander; Helen A Fletcher; Ian Poulton; Nicola C Alder; Natalie E R Beveridge; Kathryn T Whelan; Adrian V S Hill; Helen McShane (PLoS ONE)
Objectives To investigate the safety and immunogenicity of boosting BCG with modified vaccinia Ankara expressing antigen 85A (MVA85A), shortly after BCG vaccination, and to compare this first with the immunogenicity of BCG vaccination alone and second with a previous clinical trial where MVA85A was administered more than 10 years after BCG vaccination. Design There are two clinical trials reported here: a Phase I observational trial with MVA85A; and a Phase IV observational trial with BCG. These clinical trials were all conducted in the UK in healthy, HIV negative, BCG naïve adults. Subjects were vaccinated with BCG alone; or BCG and then subsequently boosted with MVA85A four weeks later (short interval). The outcome measures, safety and immunogenicity, were monitored for six months. The immunogenicity results from this short interval BCG prime-MVA85A boost trial were compared first with the BCG alone trial and second with a previous clinical trial where MVA85A vaccination was administered many years after vaccination with BCG. Results MVA85A was safe and highly immunogenic when administered to subjects who had recently received BCG vaccination. When the short interval trial data presented here were compared with the previous long interval trial data, there were no significant differences in the magnitude of immune responses generated when MVA85A was administered shortly after, or many years after BCG vaccination. Conclusions The clinical trial data presented here provides further evidence of the ability of MVA85A to boost BCG primed immune responses. This boosting potential is not influenced by the time interval between prior BCG vaccination and boosting with MVA85A. These findings have important implications for the design of efficacy trials with MVA85A. Boosting BCG induced anti-mycobacterial immunity in either infancy or adolescence are both potential applications for this vaccine, given the immunological data presented here. Trial registration ClinicalTrials.gov NCT00427453 (short boosting interval), NCT00427830 (long boosting interval), NCT00480714 (BCG alone).